Resistance Murals and Spatial Politics in the Dago Elos Agrarian Conflict: A Visual Discourse Analysis - Aprilianti Pratiwi; Nathalia Perdhani Soemantri; Ahamd Badari Burhan; Sudarto (INJECT (Interdisciplinary Journal of Communication), 2026)
Agrarian conflicts in the Dago Elos area, Bandung, not only take place in the realm of formal law and politics, but are also mediated through visual practices in residential spaces. This study aims to analyze how resistance murals function as a form of collective visual communication in responding to threats to citizens' living spaces. This research is expected to enrich the study of visual communication and urban resistance, especially in the context of urban agrarian conflict. The method used is a qualitative approach with visual discourse analysis, Gillian Rose, which includes the site of production, the site of the image, and the site of audiencing. The Data was obtained through focus group discussions with residents and artists, visual documentation, and analysis of four murals in the Dago Elos area. The results showed that murals are produced spontaneously, based on solidarity networks, and do not depend on formal structures. Visually, murals utilize a variety of communication strategies to claim living space and build a narrative of resistance. Murals also play a role in transforming everyday spaces into political arenas that are collectively accepted by citizens. This study concluded that murals do not merely represent agrarian conflicts, but become a medium for politicizing space and strengthening the collective identity of citizens.